UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL NUMBERED HEAD TOGETHER (NHT) DI KELAS V SD NEGERI 173119 PEANAJAGAR TAPANULI UTARA - Tina Sheba Cornelia Sitompul (JURNAL TEMATIK, 2018)
This research is classroom action research (PTK) using number head together (NHT) in the class grade 5 SD Negeri 173119. The subjects were fifth grade students who totaled 26 students consisting of 11 male students and 15 female students. The results of research on Cycle I obtained learning outcomes on teacher activity is with the value of 59.5% with sufficient category, while the student activity is with a value of 67.5 with enough category. Based on the established KKM that is 70, completeness of student learning outcomes obtained individually, a thorough student 19 people and 7 unfinished people. Students' learning outcomes are classically obtained by 73,08% complete student and 26,92 %  unfinished. Thus from the results of data analysis can be concluded that the implementation of learning by using cooperative learning model NHT on subjects PKn shared decision materials in class V SD Negeri 173119 Peanajagar Tapanuli Utara Lesson 2016/2017 has been categorized well and student learning outcomes have increased.